Exploring the Integration of Reading and Speaking Skills in Indonesian Language Learning through a Multimodal Digital Literacy Approach - Tintin Susilowati; Arga Mukti Wicaksana; Zahra Ardilawati; Aulia Sahara Zahwa; Moh. Rifqi Fauzi (Proceeding International Conference on Education, 2025)
This study investigates the integration of reading and speaking skills in Indonesian language learning through a Multimodal Digital Literacy (MDL) approach. A qualitative case study design was employed to explore how various text types, including written, audio, visual, and audio-visual texts that are supported by technology can be incorporated in reading and speaking skills development in order to foster literacy skills contextually and long-term retention in Indonesian language learning. The participants were 25 Indonesian Language Education students, and the learning process was conducted over ten sessions. The data were collected through a questionnaire and interviews and analysed using Miles and Huberman’s model of interactive analysis. The findings indicate that this approach could make learners more enthusiastic and promote deeper mastery of the material and skills, which aligns with the demands of present and future life. Furthermore, this approach guides learners to not only use the technology passively but also produce various creative digital products through the media transfer processes. Ultimately, engaging with and generating multimodal digital texts in language learning can build a deep learning atmosphere in the language classroom.